Pengaruh Model Problem Based Learning (PBL)-4C terhadap Kemampuan Literasi Matematis Siswa SMAN 1 Wondama - Syamsinar, Syamsinar; Asfyra, Intan Buhati (Pusat Studi Bahasa dan Publikasi Ilmiah, 2026)
This study aims to determine the effect of the Problem Based Learning (PBL) model based on 4C skills (critical thinking, creativity, collaboration, communication) on the mathematical literacy skills of high school students. This study is motivated by the low mathematical literacy skills of students and the need for learning that integrates 21st-century skills. This study uses a quantitative approach with a quasi-experimental design through a nonequivalent control group design. The research sample consisted of 63 students divided into two groups, namely 32 students in the experimental class taught using the PBL-4C model and 31 students in the control class taught with conventional learning. The research instrument was a mathematical literacy ability test given in the form of a pretest and posttest. The results of the hypothesis test using the independent sample t-test showed a significance value of 0.003 <0.05, so H₀ was rejected. In addition, the magnitude of the learning model's influence was included in the high category with an effect size value (Cohen's d) of 1.08. Thus, it can be concluded that the PBL-4C model had a significant and effective effect in improving the mathematical literacy skills of students of SMAN 1 Wondama.